Sistem Informasi Perangkat Desa (SINPERDES) Berbasis Website Dengan Metode Waterfall Dalam Pelaksanaan Pembangunan Desa - Yanti Yusman; Nurafina Siregar; Randi Rian Putra; Sri Nadriati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Website-Based Village Information System (SINPERDES) Using the Waterfall Method in Implementing Village Development The Village Information System (SINPERDES) is a technological solution designed to optimize the implementation of village development through the use of the Waterfall method in its development. The Waterfall method is a software development approach that focuses on sequential stages, starting from planning, analysis, design, implementation, to maintenance. This research aims to develop SINPERDES which is able to support village officials in managing information and village development processes more efficiently and effectively. Website-based SINPERDES was chosen as a platform to enable easier access for village communities and related stakeholders. This study involves analyzing the needs of village officials, system design, website development, and implementation in several villages as case studies. The results of this research show that Website-Based SINPERDES using the Waterfall method has succeeded in increasing information accessibility, monitoring village development, as well as coordination between village officials and the community. In addition, the use of the Waterfall method in SINPERDES development provides clarity and order in the software development process. The successful implementation of SINPERDES provides an opportunity to improve the overall quality of village development